The impact of planting scenarios on agricultural productivity and thermal comfort in urban agriculture land (case study: Tabriz, Iran) - Rahimi, Akbar; Nobar, Zahra (Frontiers in Ecology and Evolution, 2023)
Population growth is a significant challenge in developing countries because it leads to the destruction of green infrastructure and urban agriculture lands around cities, resulting in dissatisfaction with the environment. This study aims to revitalize abandoned agricultural lands within city limits due to urban planning, which can be considered a kind of green infrastructure. In Tabriz, Iran, urban agriculture and urban texture coexist, and the effect of native plant-crop combinations on micrometeorological conditions and thermal comfort on agricultural land was examined. The ENVI-MET model simulated the research area, and the output parameters were validated by comparing their values to field data. The model identified seven proposed scenarios that demonstrated higher performance in improving outdoor thermal comfort. The results showed that edible functions of deciduous plants increased with canopy height and diameter, which improved thermal comfort in high-temperature conditions. Adopting this form of planting would rejuvenate abandoned agricultural fields. Consequently, outdoor thermal comfort may be improved (1.42 predicted mean value (PMV) reduction in the land without plants and a 1.37 PMV reduction in the agriculture land simulation), leading to the rehabilitation of urban agricultural lands that have lost their function in developing cities. These research findings can be utilized to help address the impacts of population growth on green infrastructure and urban agriculture lands.